Pengaruh pemberian minuman lidah buaya terhadap kadar antioksidan total dan persentase lemak tubuh pada sindrom metabolik - Silitonga, Marisi Elizabeth R.; Nugroho HS, K. Heri; Tjahjono, Kusmiyati; Widyastiti, Nyoman Suci; Afifah, Diana Nur (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2018)
Background: Metabolic syndrome is related to glucose metabolism disturbance (hyperglycemia), lipid (dyslipidemia), high blood pressure, and central obesity. Metabolic syndrome implicates to heart attack, diabetes mellitus, hypertension, and death. Aloe vera, well known rich of polyphenol and vitamin, has a pharmacological effect to improve insulin resistance, chronic inflammation, and oxidative stress.Objective: To prove the effect of Aloe vera-based drink toward total antioxidant concentration improvement and body fat percentage reduction in metabolic syndrome subjects.Methods: Thus study was pre-post randomized true experimental study with control group design. The subjects were divided by 2 groups, treatment group (n=19) and control group (n=19). Treatment group was given 165 g/d Aloe vera-based drink for 30 days. Both of groups were given nutrition education about metabolic syndrome management. Total antioxidant concentration and body fat percentage were assessed pre-post-test by ABTS and BIA respectively, while food intake and activity were assessed by 24-h recall and GPAQ respectively. Independent t-test and Mann Whitney test were used to compare before and after treatment between control and treatment group.Results: Total antioxidant concentration significantly improved (p=0.00) in treatment group from 1.2 to 2.0 mmol/L, while total antioxidant concentration decreased from 1.4 to 1.3 mmol/L (p=0.074) in this control group. Moreover, there was significant difference of total antioxidant between treatment and control groups in the end of study (p=0.00). Furthermore, body fat percentage was reduced significantly from 32.8 to 32,4 mmol/L (p=0.005) in treatment group, while the reduction of body fat percentage in control group was not significant from 33.1 to 33,4 mmol/L (p=0.100). There was no difference of body fat percentage between two groups after intervention (p=0.358).Conclusion: Aloe vera-based drink improved total antioxidant concentration in metabolic syndrome subjects.